Conversion to dementia in mild cognitive impairment diagnosed with DSM‐5 criteria and with Petersen's criteria. (21st December 2015) - Marcos, G.; Santabárbara, J.; Lopez‐Anton, R.; De‐la‐Cámara, C.; Gracia‐García, P.; Lobo, E.; Pírez, G.; Menchón, J. M.; Palomo, T.; Stephan, B. C. M.; Brayne, C.; Lobo, A.; et al.
Abstract : Objective: In a background of revision of criteria for states of increased risk for progression to dementia, we compare the conversion rate to dementia and Alzheimer's disease (AD) of mild cognitive impairment (MCI) as diagnosed using DSM‐5 (DSM‐5‐MCI) and Petersen's (P‐MCI) criteria. Method: A population representative cohort of 4057 dementia‐free individuals 55+ years of age was followed up at 2.5 and 4.5 years in Zaragoza, Spain (ZARADEMP). Using the Geriatric Mental State‐ AGECAT for assessment, research psychiatrists diagnosed DSM‐5‐MCI and P‐MCI following operationalized criteria. 'Conversion rate' (CR), 'annual conversion rate' (ACR), and incidence rate (IR) were calculated along with incidence rate ratio (IRR) to compare the performance of the intermediate cognitive definitions. Results: At 4.5‐year follow‐up, in individuals aged 65+ years, ACRs for non‐cases, P‐MCI, and DSM‐5‐MCI were 0.8, 1.9 and 3.4, respectively, for global dementia. The IRRs were 2.9 and 5.3 for P‐MCI and DSM5‐MCI, respectively, being the non‐cases the reference category. The corresponding values were slightly lower for AD. Conclusion: Conversion rate to dementia and AD was higher using DSM‐5‐MCI criteria than using Petersen's criteria. However, prediction of the construct still has some way to go, as most MCI individuals did not convert at 4.5‐year follow‐up.